The Determinants of Stunting in the Under-five in Three Municipalities in the Special Capital Region of Jakarta - Permatasari, Tria Astika Endah; Chairunnisa, Chairunnisa; Djarir, Hernani; Herlina, Lily; Fauziah, Munaya; Andriyani, Andriyani; Chadirin, Yudi (UI Scholars Hub, 2023)
The COVID-19 pandemic has impacted the global decline in public health status. This study aimed to analyze the determinants of stunting in the under-five in three municipalities in the Special Capital Region of Jakarta, Indonesia. A cross-sectional study was conducted in August-December 2020 with 460 pairs of mothers and children selected by simple random sampling. Stunting was measured using a conventional anthropometric index (length/height-for-age), and anthropometric failure was measured using the Composite Index of Anthropometric Failure. The prevalence of stunting, underweight, and wasting was 41.5%,35%, and 19.8%, respectively, and 62% of the under-five experienced anthropometric failure. The dominant factor associated with stunting was immunization record (p-value = 0.011; AOR = 2.360; 95%CI = 1.218–4.573). Children who did not receive complete basic immunization were at a 2.4 times greater risk of stunting than children who received complete basic immunization. The dominant factors associated with underweight, wasting, and anthropometric failure were the father's educational level, mother's occupation, and balanced nutrition practice. Increasing coverage of complete basic immunization, improving balanced nutrition practices and socioeconomic conditions is necessary to prevent undernutrition, especially stunting.